The “Honor Killing” of Social Media Star Qandeel Baloch: Technological Change, the Changing Roles of Women, and Grassroots Backlash - Smith Nash, Susan (IJRDO - Journal of Social Science and Humanities Research, 2016)
The murder of Qandeel Baloch was just one of hundreds of "honor killings" that take place in Pakistan every year. However, because she was an outspoken social media star with more than 700,000 followers, her death brought attention to how social media has brought new focus to the evolving roles of women, has resulted in a grassroots backlash. At the same time, an examination of the specific accomplishments of Qandeel Baloch provide insight into a deeply and fascinatingly subversive artist who essentially invented herself, appropriating the tools and techniques of Western media sensations, and subsuming them in her own context(s). Further, an evaluation of what occurs in so-called "honor killings" makes it clear that "honor cultures" and violence toward women are universal, and the lessons learned in the death of Qandeel apply across the board, globally.